MS‐routing‐Gi: routing technique to minimise energy consumption and packet loss in WSNs with mobile sink. Issue 6 (1st November 2018) - El Alami, Hassan; Najid, Abdellah
Abstract : Energy efficiency is a major factor in designing wireless sensor networks (WSNs). Clustering design and grid‐based scheme are one of the techniques to save energy in WSNs. However, for a mobile sink in WSNs, packet loss rate that occurs due to the sink mobility is also a significant challenge. Here, an enhanced routing‐G i protocol for a mobile sink in WSNs has been proposed to not only enhance energy efficiency but also minimise the packet loss rate. Simulation results show that the proposed protocol is more efficient than the previous protocols in terms of the network lifespan, energy efficiency, and packet delivery ratio. Thus, the proposed approach in this work could further be adapted to investigate highly mobility of sink in WSNs.